2022
DOI: 10.18502/ijm.v14i5.10958
|View full text |Cite
|
Sign up to set email alerts
|

Serotype distribution and antibiotic resistance of Streptococcus pneumoniae isolates collected from unvaccinated children with pneumonia at a province in central Vietnam

Abstract: Background and Objectives: Identification of pnemococcal serotypes and antimicrobial resistance provides helpful infor- mation for the use of suitablevaccines and antibiotics; however, very limited data is available on these issues in Vietnam. The present study aimed to find the serotype distribution and drugresistance patterns of Streptococcus pneumoniae isolated from unvaccinated children less than 5 years of age with pneumonia at a province in centre Vietnam. Materials and Methods: A total of 126 clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This is also a limitation of this study, which is being implemented as a follow-up study in this area. A study in a northern province of Vietnam identified eight serotypes of S. pneumoniae isolated from unvaccinated children under 5 years of age with pneumonia, including 19F, 23F, 19A, 6A/B, 15A, 9V, 11A, and 14 ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is also a limitation of this study, which is being implemented as a follow-up study in this area. A study in a northern province of Vietnam identified eight serotypes of S. pneumoniae isolated from unvaccinated children under 5 years of age with pneumonia, including 19F, 23F, 19A, 6A/B, 15A, 9V, 11A, and 14 ( 25 ).…”
Section: Discussionmentioning
confidence: 99%